The development of the EULAR–OMERACT rheumatoid arthritis MRI reference image atlas. (12th January 2005) - Bird, P; Conaghan, P; Ejbjerg, B; McQueen, F; Lassere, M; Peterfy, C; Edmonds, J; Shnier, R; O'Connor, P; Haavardsholm, E A; Emery, P; Genant, H; et al.
Abstract : Based on a previously developed rheumatoid arthritis MRI scoring system (OMERACT 2002 RAMRIS), the development team agreed which joints, MRI features, MRI sequences, and image planes would best illustrate the scoring system in an atlas. After collecting representative examples for all grades for each abnormality (synovitis, bone oedema, and bone erosion), the team met for a three day period to review the images and choose by consensus the most illustrative set for each feature, site, and grade. A predefined subset of images (for example, for erosion—all coronal slices through the bone) was extracted. These images were then re-read by the group at a different time point to confirm the scores originally assigned. Finally, all selected images were photographed and formatted by one centre and distributed to all readers for final approval.